Fighting counterfeiting: importance of enforcement of intellectual property rights - Mohamed, Khadijah; Wahid, Ratnaria (International Association of IT Lawyers (IAITL), 2014)
Counterfeiting has currently been labelled as the crime of the twenty-first century.It has evolved into a much more lucrative business in very sophisticated ways.While there are many contributing factors to the proliferation of counterfeiting in recent years, the only real area where the government can make a difference is in setting up a responsive legal system that includes good enforcement.The aim of this paper is to examine the scale of counterfeiting activity derived from the seizure data issued by the World Customs Organization, emphasizing on the worldwide scenario.This is followed by examination on the motivations behind counterfeiting activity to identify gap in the existing enforcement mechanisms so that recommendations can be made to improve the competency of those mechanisms to address counterfeiting.The paper then critically examines and relates the reasons of why effective enforcement is necessary in the fight against counterfeiting.